Implementing College and Career Readiness: Critical Dimensions for Youth with Severe Disabilities. (September 2017) - Morningstar, Mary E.; Zagona, Alison L.; Uyanik, Hatice; Xie, Jingrong; Mahal, Stephanie
Focused attention to the Common Core State Standards (CCSS) and college and career readiness (CCR) has been attributed to increased secondary school reform efforts directed at ensuring all students graduate high school prepared for adulthood. To successfully experience college and careers, students must have the knowledge, skills, and experiences associated with engagement in core academics, as well as essential nonacademic competencies such as growth mindsets, problem-solving, and interpersonal engagement. This study sought out insights and perspectives from national experts to understand the skills, opportunities, and supports needed to ensure students with severe disabilities are college and career ready. The study offers research results focused on initial insights supportive of inclusive postsecondary outcomes for youth with severe disabilities.